Nonfatal acute myocardial infarction in Costa Rica: modifiable risk factors, population-attributable risks, and adherence to dietary guidelines - Kabagambe, Edmond K. (2007)
Disability and mortality resulting from cardiovascular disease (CVD) are on the rise in many developing countries, partly because of the nutritional transition and westernization of lifestyles. Developing countries account for 80% of the global CVD burden. In 2002, the number of health-years of life lost to heart disease including myocardial infarction (MI) per 1000 people in developing countries was between 6 and 20 for countries such as Costa Rica, Uganda, Croatia, Nigeria, Indonesia, and India, whereas for developed countries, they were 5 for Australia, 5 for Canada, 7 for the United Kingdom, and 8 for the United States. These numbers suggest poor quality of secondary prevention and lack of primary CVD prevention in developing countries. Recent data show that primary prevention could reduce CVD deaths by 4 times the reduction achieved through secondary prevention.